To invent a state of art technology on web-based Hanyu Pinyin instruction to facilitate self learning Mandarin for non native Mandarin learners / Lim Soo Giap and Ong Sheau Fen - Lim Soo Giap; Ong Sheau Fen (Research Management Institute (RMI), 2010)
Hanyu Pinyin (Romanised Mandarin) is used in the teaching and learning of Mandarin as a third language in UiTM. As the time allocated for teaching Hanyu Pinyin is insufficient for learners many of whom are exposed to Mandarin for the first time to satisfactorily comprehend the intricacies of its sound system, therefore it is necessary to devise some self-learning materials for learners to enable them to control and monitor their learning process in the absence of facilitator. In order to create an environment conducive for self learning Hanyu Pinyin, a web-based instruction is suggested to incorporate into the curriculum. This is an internet enabled web-based instruction. It generally applies to any kind of instructional materials delivered over the Internet accessed by browser-equipped computer users. The specify objective of this project is to design a web based instruction (WBI) especially for Bumiputra Mandarin learners. The WBI is the instructional materials that are used in the learning system that involves the network operation center (NOC), the WWW resources, the learners, instructors and the regularly conducted lectures of fulltime teaching staff. This instruction is designed on the basis of ISD (Instructional system design) methodology. This approach involves four phases; 1.analysis and design, 2.development, 3.implementation and 4.evaluation of the instruction. Eventually, the effectiveness of the instruction was evaluated. This research also discusses some limitations and constraints that were discovered, at the sometimes some recommendations are proposed to overcome the limitations for the future research.